Evaluation of the effect of carvedilol orodispersible tablets on ischemia-reperfusion injury and flap viability in rats: An in vivo study - Tokgonul, Serkan; Ozyilmaz, Emine Dilek; Comoglu, Tansel; Gurbuz, Manolya Mujgan; Topal, Burcu Dogan; Kocak, Fatma Emel; Ozakpinar, Huelda Rifat (Wiley-V C H Verlag Gmbh, 2024)
Flap surgery is an integral part of plastic surgery, and ischemia-reperfusion (I/R) injury significantly affects the viability of the flap. Carvedilol (CRV), a nonselective beta-blocker with alpha-1 blocking and antioxidant properties, and known for its potential in reducing I/R damage, was chosen as the active substance for our study. The aim of this study was to investigate the vasodilator and antioxidant effects of CRV on rat inferior epigastric artery skin flap using orally disintegrating tablets (ODTs). The optimized ODT formulation was subjected to in vivo experiments using Sprague-Dawley female rats (n = 24) divided into three groups: Group I (control, I/R), Group II (treatment, I/R + CRV), and Group III (treatment, I/R), I/R + CRV ODT). Reperfusion was then observed following the release of the microclamp from the pedicle, and the flap was then re-adapted to its original position. Control rats were given oral isotonic solution via gavage and were subjected to 8 h of ischemia and 12 h of reperfusion. Group II was given 2 mg/kg CRV oral tablets for 7 days before and after surgery. Group III was given 2 mg/kg/day CRV ODT for the same period. Biopsies were taken from the flap and histopathological and biochemical analyses including superoxide dismutase, glutathionenitric oxide, malondialdehyde, paraoxonase 1, total oxidant, and total antioxidant capacities were performed. This study demonstrates that CRV ODTs significantly increased flap viability by approximately 25% compared to the control group, highlighting their promising therapeutic potential. The vasodilator and antioxidant effects of carvedilol on rat inferior epigastric artery skin flap were investigated using orally disintegrating tablets (ODTs). ODT formulations were developed and their in vitro properties were evaluated. The optimized formulation was subjected to in vivo experiments using Sprague-Dawley female rats.image
Keywords: carvedilol; flap viability; ischemia-reperfusion injury; orodispersible tablets